2016
DOI: 10.1111/jpi.12354
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin modulates neonatal brain inflammation through endoplasmic reticulum stress, autophagy, and miR‐34a/silent information regulator 1 pathway

Abstract: Maternal infection/inflammation represents one of the most important factors involved in the etiology of brain injury in newborns. We investigated the modulating effect of prenatal melatonin on the neonatal brain inflammation process resulting from maternal intraperitoneal (i.p.) lipopolysaccharide (LPS) injections. LPS (300 μg/kg) was administered to pregnant rats at gestational days 19 and 20. Melatonin (5 mg/kg) was administered i.p. at the same time as LPS. Melatonin counteracted the LPS sensitization to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
90
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 70 publications
(123 reference statements)
10
90
0
2
Order By: Relevance
“…Although the mechanism(s) underlying hypothermia/ melatonin cooperation in reducing brain injury was not the aim of this study, it is worth recalling that, by acting via a specific cell membrane and nuclear receptors, melatonin achieves powerful neuroprotective effects via antioxidant, antiapoptotic, and anti-inflammatory processes [13,29], and by promoting neuronal and glial development [30]. Additional indirect antioxidant effects of melatonin include the upregulation of antioxidant enzymes and crucially the preservation of mitochondrial integrity [12,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanism(s) underlying hypothermia/ melatonin cooperation in reducing brain injury was not the aim of this study, it is worth recalling that, by acting via a specific cell membrane and nuclear receptors, melatonin achieves powerful neuroprotective effects via antioxidant, antiapoptotic, and anti-inflammatory processes [13,29], and by promoting neuronal and glial development [30]. Additional indirect antioxidant effects of melatonin include the upregulation of antioxidant enzymes and crucially the preservation of mitochondrial integrity [12,31].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin is a potent scavenger of reactive oxygen species with anti-inflammatory effects in conditions associated with oxidative stress as well as immunomodulatory effects in the presence of an exacerbated immune response [11,12]. When given before or immediately after hypoxia-ischemia in different models of perinatal brain injury, melatonin showed neuroprotective effects [13][14][15]. Melatonin also appeared effective in different neonatal pathological conditions, including neonatal sepsis, bronchopulmonary dysplasia, and neonatal asphyxia [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In a rat scopolamine toxicity model of ADlike memory losses, melatonin reversed an increase of miR-124 and thereby corrected the level of the targeted Egr1 (early growth response protein 1) mRNA [27]. In another AD model, Aβ [25][26][27][28][29][30][31][32][33][34][35] peptide added to primary cortical neurons caused downregulation miR-132, an effect that was also reversed by melatonin. The normalization of miR-132 is insofar of importance, as this miRNA transmits anti-apoptotic and other protective properties known from melatonin [28].…”
Section: Discussionmentioning
confidence: 99%
“…In neonatal brain inflammation induced in rats by bacterial lipopolysaccharide (LPS), this pro-inflammatory agent upregulated miR-34a, but downregulated miR-146a, and miR-126. Again, these changes were corrected by melatonin, along with reduction in ER stress and autophagy as well as reversal of sirtuin 1 downregulation [29]. With some likelihood, other data on inflammation may have resulted from transfer of miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…In a rat scopolamine toxicity model of AD-like memory losses, an increase of miR-124 was observed that was reversed by melatonin, along with correction of the targeted Egr1 mRNA [106]. Lipopolysaccharide (LPS)-induced neonatal brain inflammation in rats caused changes in miR-34a, miR-146a, and miR-126, along with reduction of SIRT1 expression, effects that were reversed by melatonin [107]. Premature senescence of cardiac progenitor cells by H 2 O 2 was prevented by melatonin by maintaining the expression levels of lncRNA H19 and its derivative miR-675 [108].…”
Section: Noncoding Rnas Exosomes and Ncrna Links Between Epigeneticmentioning
confidence: 99%